EFEKTIVITAS PBL DAN KELUBA BERBASIS KEARIFAN LOKAL KUDUS UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD - Prafita, Zakyya Nur Danamarthira; Cahyani, Marcelina Harum; Aliatul Muna, Deswita Revaleno; Amaliyah, Fitriyah (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
This study aims to determine the effectiveness of the Problem Based Learning model assisted by Keluba media based on Kudus local wisdom in improving the mathematical problem solving ability of elementary school students. Background This research is the low ability to solve the mathematical problem of grade IV students of SD Negeri 3 Ngembal Kulon. This study uses a quantitative approach with the pre-experimental method and one group pretest-posttest design. The population was all students of grade IV SD Negeri 3 Ngalambal Kulon. The research sample is all 4th grade students totaling 9 people. The instrument used was a pretest and posttest test in the form of mathematical story questions. The data were analyzed using a normality test, paired sample t-test, and ngain test. The results showed that the average pretest value of 48.22 increased to 93.56 in posttest. The paired sample t test shows a significance value of 0.001 <0.05, which means there is a significant difference between the pretest and posttest results. The average value of gain is 0.8825> 0.76. These results indicate that the application of the PBL model assisted by the Kudus local wisdom-based media is effective in improving the ability to solve students' mathematical problems.